A systematic review of the evidence base for the Lightning Process - Parker, Phil; Aston, Jacqui; De Rijk, Lisa (Elsevier, 2021)
The Lightning Process (LP), a mind-body training programme, has been applied to a range of health problems and disorders. Studies and surveys report a range of outcomes creating a lack of clarity about the efficacy of the intervention. This systematic review evaluates the methodological quality of existing studies on the LP and collates and reviews its reported efficacy. Five databases, PsycINFO, PubMed, CINAHL, Embase, ERIC (to September 2018), and Google and Google Scholar were searched for relevant studies. Studies of the LP in clinical populations published in peer-reviewed journals or in grey literature were selected. Reviews, editorial articles and studies/surveys with un-reported methodology were excluded. Searches returned 568 records, 21 were retrieved in full text of which 14 fulfilled the inclusion criteria (ten quantitative studies/surveys and four qualitative studies). The review identified variance in the quality of studies across time; earlier studies demonstrated a lack of control groups, a lack of clarity of aspects of the methodology and potential sampling bias. Although it found a variance in reported patient outcomes, the review also identified an emerging body of evidence supporting the efficacy of the LP for many participants with fatigue, physical function, pain, anxiety and depression. It concludes that there is a need for more randomised controlled trials to evaluate if these positive outcomes can be replicated and generalised to larger populations.